A new Leptobrachella (Anura: Megophryidae) from the Cardamom Mountains of Cambodia - Stuart, Bryan L.; Rowley, Jodi J. L. (Zootaxa, 2020)
The species-rich, megophryid frog genus Leptobrachella Smith, 1925 is distributed throughout the uplands of mainland Southeast Asia but is conspicuously absent from the Cardamom Mountains of southwestern Cambodia, where it has been known only by a single, undetermined metamorphic specimen collected nearly two decades ago. We report two adult female specimens of Leptobrachella collected a decade later at a second locality in the Cardamom Mountains and use mitochondrial DNA, nuclear DNA, and morphology to show that it represents a distinct species. Leptobrachella neangi sp. nov., named after its collector, is most closely related in mitochondrial and nuclear DNA to L. fuliginosa (Matsui, 2006) and L. melanoleuca (Matsui, 2006) from western Thailand, but has uncorrected pairwise distances of 8.69–10.99% in a mitochondrial 16S gene fragment from its two sister species. The new species is also readily distinguished from these and other congeners by having the combination of (1) SVL 35.4–36.3 mm in two adult females, (2) distinct dorsolateral glandular line absent, (2) belly transparent, immaculate purplish gray in life, creamy white in preservative, (3) dark inguinal blotch absent, (4) tympanum with black coloration extending from line under supratympanic fold, (5) dorsal skin with small, irregular bumps and ridges, and (6) iris coppery orange around pupil, fading to gold at periphery, not distinctly bicolored. The new species is the first named Leptobrachella from the Cardamom Mountains and the third from Cambodia.